A survey of the relevance of control systems for PEM fuel cells - Ali, E A Mohamed; Abudhahir, A (2011 International Conference on Computer, Communication and Electrical Technology, 2011)
This survey is the revelation of the importance of a polymer electrolyte membrane fuel cell(PEMFC) for energy conversion and the need to have a knowledge about the control system for the effective functioning of a PEM fuel cell. The recent general observation of public, policy makers, entrepreneurs, technology developers and scientists is the awareness of environmental protection and the fast growth of world energy consumption that leads them to search for alternative means to carry and convert energy. It is predicted that a fuel cell will be a promising device and it can be a substitute for the conventional energy converters. Comparing with the other types of fuel cells, PEM fuel cells are considered as a possible answer for the environmental and energy problems, and are expected soon to become the most valuable futuristic energy converters for automotive, stationary, and portable applications, because of their high-energy density at low operating temperatures, quick start-up and zero emission. However, the performance, stability, reliability and cost for the present fuel cell technology are not enough to replace conventional energy converters. A number of fundamental problems must be overcome to improve their performance and reduce their cost. The fundamental crises which need to be taken care of are the maintenance of fuel and air flow rate at an optimum level during load variation, start-up and shutdown and water management, temperature management and pressure regulation. In short, this survey is the evaluation of the recent developments in PEM fuel cell and the rectification of the fundamental problems using a detailed analysis of a control system.